Estimation of effectiveness factor for arbitrary particle shape and non-linear kinetics - Mariani, Nestor Javier (2008)
A one-dimensional model, called generalized cylinder (GC), is employed to analyze the diffusion-reaction problem in catalytic pellets of different shapes and nonlinear kinetics. The fitting parameter (ó) of the GC model was adjusted by matching the behavior of the actual pellet at high reaction rates. The errors of the GC model, considering five different kinetic expressions (isothermal zero and second order, isothermal Langmuir-Hinshelwood-Hougen-Watson type, first order exothermic, and first order endothermic) and four different catalytic pellet shapes turned out to be less than 3.5%.